Recent Advances and Future Trends in the Detection of Contaminants by Molecularly Imprinted Polymers in Food Samples - Gao, Mingkun; Gao, Yuhang; Chen, Ge; Huang, Xiaodong; Xu, Xiaomin; Lv, Jun; Wang, Jing; Xu, Donghui; Liu, Guangyang (Frontiers in Chemistry, 2020)
Drug residues, organic dyes, heavy metals, and other chemical pollutants not only cause environmental pollution but also have a serious impact on food safety. A timely and systematic summary of the latest scientific advances is of great importance for the development of new detection technologies. In particular, molecularly imprinted polymers (MIPs) can mimic antibodies, enzymes, and other biological molecules to recognize, enrich and separate contaminants, with specific recognition, selective adsorption, high affinity, and strong resistance characteristics. Therefore, MIPs have been widely used in chemical analysis, sensing, and material adsorption. In this review, we first describe the basic principles and production processes of molecularly imprinted polymers. Secondly, an overview of recent applications of molecularly imprinted polymers in sample pre-treatment, sensors, chromatographic separation, and mimetic enzymes is highlighted. Finally, a brief assessment of current technical issues and future trends in molecularly imprinted polymers is also presented.